An Empirical Analysis of Short Run and Long Run Relationships between Energy Consumption, Technology Innovation and Economic Growth in Saudi Arabia - Akinwale, Yusuf Opeyemi (International Journal of Energy Economics and Policy, 2018)
This study investigates the short- and long-run relationships between energy consumption, technology innovation and economic growth in Saudi Arabia. The direction of causality between them was also determined using Granger causality. The data covers the period between 1980 and 2015, and autoregressive distributed lag (ARDL) was used for analysis as the series consist of the mixture of I(0) and I(1) order of integration. The results reveal that the variables are cointegrated which establish the existence of long run relationships between them. In the long-run, technology innovation has a negative effect on energy consumption while economic growth has a positive effect on energy consumption. Similar result was found in the short run. The results of the Granger causality show a unidirectional causality runs from technology innovation and economic growth to energy consumption. The results of this study support intensive investment in R&D and technology innovation by Saudi government and private companies as well as the implementation of energy efficiency and conservation policies to reduce energy demand, as this would not hamper the economic growth of Saudi Arabia. Government should fully explore the use of renewable energy sources and technologies such as solar and wind to bring about sustainable development in the Country. Keywords: Energy consumption; Technology innovation; Economic growth; Saudi Arabia; Conservation policies, ARDL; Vision 2030 JEL Classifications: B13, C01, O32, Q43, Q54, Q58